On compactness and metrizability of nuclear spaces of manifolds - Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove a theorem on the sequential compactness of the so-called nuclear space of an arbitrary topological manifold.